2022
DOI: 10.1186/s12967-022-03383-x
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical validation of full HR-HPV genotyping HPV Selfy assay according to the international guidelines for HPV test requirements for cervical cancer screening on clinician-collected and self-collected samples

Abstract: Background According to international guidelines, Human Papillomavirus (HPV) DNA tests represent a valid alternative to Pap Test for primary cervical cancer screening, provided that they guarantee balanced clinical sensitivity and specificity for cervical intraepithelial neoplasia grade 2 or more (CIN2+) lesions. The study aimed to assess whether HPV Selfy (Ulisse BioMed – Trieste, Italy), a full-genotyping HPV DNA test that detects and differentiates 14 high-risk HPV (HR-HPV) types, meets the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 47 publications
(36 reference statements)
2
16
0
Order By: Relevance
“…This may rise suspicion of a certain degree of histological over-classification. Nonetheless, we verified the data matrices in Table 2 in Avian et al [ 1 ] and confirm the correctness of the non-inferiority statistics (Table 1 ).
Fig.
…”
supporting
confidence: 87%
See 4 more Smart Citations
“…This may rise suspicion of a certain degree of histological over-classification. Nonetheless, we verified the data matrices in Table 2 in Avian et al [ 1 ] and confirm the correctness of the non-inferiority statistics (Table 1 ).
Fig.
…”
supporting
confidence: 87%
“…In primary cervical cancer screening, it is crucial to use only hrHPV tests that are clinically validated according to international guidelines in order to reduce the risks of missing relevant disease and of over-treatment. In the recent J Transl Med [ 1 ] paper, Avian et al concluded that the HPV Selfy assay (Ulisse BioMed, Trieste, Italy) fulfils international validation criteria for hrHPV testing on clinician-collected cervical samples (Meijer guidelines) [ 2 ] as well as by extension on self-collected vaginal samples (VALHUDES) [ 3 ]. Our perception is that the study by Avian et al has certain limitations that are worthy of consideration and which may call into question certain conclusions.…”
mentioning
confidence: 99%
See 3 more Smart Citations